2014
DOI: 10.1007/s10571-014-0085-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic Effect of Taxodione on Serum/Glucose Deprivation-Induced PC12 Cells Death

Abstract: Taxodione, a diterpenoid from the roots of Salvia chorassanica Bunge, possesses cytotoxic, apoptotic, and antimicrobial activity. This study was designed to investigate the protective effects of taxodione on serum/glucose deprivation-induced ischemic injury in PC12 cells and related mechanisms. In an in vitro model of ischemia, PC12 cells were exposed to serum and glucose deprivation for 6 and 18 h. The protective effects of the methanol extract of S. chorassanica and taxodione were assessed using alamarBlue(®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Mousavi et al reported that intracellular ROS production significantly increased when PC12 cells were exposed to SGD condition (21). Other research also referred to the role of ROS production in SGD insult (25,26). In this study, SGD caused a major increase in ROS production that is in agreement with other reports.…”
Section: Discussionsupporting
confidence: 92%
“…Mousavi et al reported that intracellular ROS production significantly increased when PC12 cells were exposed to SGD condition (21). Other research also referred to the role of ROS production in SGD insult (25,26). In this study, SGD caused a major increase in ROS production that is in agreement with other reports.…”
Section: Discussionsupporting
confidence: 92%
“…***p < .001 vs. control group, # p < .05, ## p < .01, ### p < .001 vs. OGD/R group. members which leads to activation of the mitochondria-dependent caspase signaling pathway (Mousavi et al, 2010;Shafaei-Bajestani et al, 2014). Bax over-expression can promote the apoptosis (Gao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We modified the experimental conditions from previous reports for the reperfusion/hypoglycemic condition. The previous studies used oxygen-glucose deprivation for 4 hours/reperfusion for 20 hours [ 15 ]; serum and glucose deprivation for 6 and 18 hours [ 34 35 ]; and 2.5 hours oxygen-glucose deprivation, followed by a 24-hour reoxygenation period [ 36 ] to study PC-12 cell apoptosis. We used glucose deprivation for 1 hour/reperfusion for 23 hours and glucose deprivation for 6 hours/reperfusion for 18 hours, and continued for 5 days to evaluate the involvement of FOXO in repeated glucose deprivation/reperfusion, and compared them with the controls not exposed to hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%